Penempatan Aspek Makna dan Makna Emotif dalam Tuturan (Tuduhan, Dakwaan, Tuntutan, Pembelan Diri) Selebritis Indonesia Dalam Berbagai Kasus di Media dan Implementasinya di SMA - Mahmudah, Siti, Drs. Andi Haris Prabawa, M.Hum (2017)
The purpose of this study, namely, (1) to describe aspects of the meaning contained in the speech (accusations, charges, demands, pembelan self) Indonesian celebrities in various cases in the media. (2) to describe the emotive meaning in speech (accusations, charges, demands, pembelan self) Indonesian celebrities in various cases in the media. Sources of data in this study is the infotainment media celebrity event in the latest edition, 2016. In the case of data collection researchers used a technique see and record. The theory used is Pateda theory about the aspect of meaning. This type of research is descriptive qualitative. Researchers analyzed using pragmatic and match technique. This study shows that the aspect of meaning in speech (accusations, charges, demands, pembelan self) Indonesian celebrities in various cases in the media. Aspect consists of a sense of meaning, feeling, tone, and purpose. Emotive meaning in speech (accusations, charges, demands, pembelan self) Indonesian celebrities in various cases in the media, appearing in the form of the artist's response to cases of them. Results of research on speech and meaning in a discourse can be implemented in learning Indonesian language and literature for Specialization in Linguistics and Cultures class XII High School in accordance with the second semester of 2013. The curriculum speech in Indonesian language learning in high school can be implemented with basic competency "Identifying the connotative meaning and denotative, lexical, figurative and straightforward, referential meaning and significance nonreferensial, general and specific meanings, change, a shift in the meaning of the word, and the meaning of the word relationship ". The discourse used can be implemented on sentence comprehension learning of the use of meanings that exist in every dialogue. Key words: meaning aspect, emotive meaning, utterance